GAMBARAN PEMERIKSAAN BRAINSTEM AUDITORY EVOKED POTENTIAL PADA PEKERJA TERPAJAN BISING DAN GETARAN - Nova Dian Lestari*, Manfaluthy Hakim*, Fitri Octaviana*, Widayat Alviandi**,Joedo Prihartono*** (Neurona Majalah Kedokteran Neuro Sains, 2010)
INTRODUCTION NOISE AND VIBRATION ARE BELIEVED TO HAVE A SYNERGY EFFECT WHICH CREATES HEARING PROBLEMS THE EXPERIMENTAL RESEARCH FOUNDS THAT NOISEINDUCED HEARING DISORDERS NOT ONLY DAMAGE THE HAIR CELLS WHICH FUNCTION AS HEARING RECEPTOR BUT ALSO CAUSED NEURAL DEGENERATION IN THE AUDITORY PATHWAYS NOT MUCH ATTENTION IS GIVEN TO THE NOISEINDUCED AUDITORY PATHWAYS DISORDERS NOWADAYS BRAINSTEM AUDITORY EVOKED POTENTIAL BAEP EXAMINATION IS ONE OF MODALITIES WHICH CAN BE USED TO ASSESS THE AUDITORY PATHWAYS FUNCTIONAL DISORDERS